Quantitative Analysis Method for Tencel A100 and Viscose Fiber Mixtures. Issue 2 (March 2017) - Liu, Jinrui; Gao, Youjun; Zhang, Xiangli; Zhao, Sumin
This paper presents a quantitative analysis method for determining Tencel A100 (lyocell) fiber and viscose fiber content, and that of their blends, using a formic acid/zinc chloride dissolution procedure. Ultrasonic treatment was used in this procedure. A standard curve was generated to measure fiber content. This minimized errors caused by laboratory temperature changes, reagents and instruments used, and human factors.